Protective effects of feed additives on broiler chickens exposed to aflatoxins-contaminated feed: a systematic review and meta-analysis - Putra, Reza Pratama; Astuti, Dian; Respati, Adib Norma; Ningsih, Niati; Triswanto; Yano, Aan Andri; Gading, Besse Mahbuba We Tenri; Jayanegara, Anuraga; Sholikin, Mohammad Miftakhus; Hassim, Hasliza Abu; Azmi, Amirul Faiz Mohd; Adli, Danung Nur; et al. (Springer, 2023)
Aflatoxin contamination in feed is a common problem in broiler chickens. The present systematic review and meta-analysis examined the impact of aflatoxin-contaminated feed and the efficacy of various feed additives on the production performance of broiler chickens fed aflatoxin-contaminated feed (AF-feed). A total of 35 studies comprising 53 AF-feed experiments were selected following PRISMA guidelines. Feed additives included in the analyses were toxins binder (TB), mannan-oligosaccharides (MOS), organic acid (OA), probiotics (PRO), protein supplementation (PROT), phytobiotics (PHY), and additive mixture (MIX). Random effects model and a frequentist network meta-analysis (NMA) were performed to rank the efficacy of feed additives, reported as standardized means difference (SMD) at 95 confidence intervals (95 CI). Overall, broiler chickens fed AF-feed had significantly lower final body weight (BW) (SMD = 198; 95 CI = 198 to 238) and higher feed conversion ratio (SMD = 0.17; 95 CI = 0.13 to 0.21) than control. Treatments with TB, MOS, and PHY improved the BW of birds fed AF-feed (P < 0.05) to be comparable with non-contaminated feed or control. Predictions on final BW from the broiler-fed aflatoxin-contaminated diet were 15 lower than the control diet. Including feed additives in the aflatoxins diet could ameliorate the depressive effect. Remarkably, our network meta-analysis highlighted that TB was the highest-performing additive (P-score = 0.797) to remedy aflatoxicosis. Altogether, several additives, especially TB, are promising to ameliorate aflatoxicosis in broiler chickens, although the efficacy was low regarding the severity of the aflatoxicosis.